2016
DOI: 10.1109/jstars.2015.2478120
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Agricultural Grasslands With Time Series of X-Band Repeat-Pass Interferometric SAR

Abstract: This study evaluates the potential of X-band interferometry for monitoring of agricultural grasslands. Time series of HH-polarization COSMO-SkyMed 1-day repeat-pass interferometric SAR (InSAR) pairs is analyzed in regard to detecting mowing events, and assessing vegetation height and biomass on grasslands. The time series of four InSAR pairs was analyzed in regard to the ground reference data collected during an extensive campaign covering 11 agricultural grasslands. The calculated temporal interferometric coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
5
27
0
Order By: Relevance
“…Increase of coherence after a mowing event is in line with a similar previous study that was based on X-band data and 1-day interferometric pairs [27]. In contrast to that study, the use of C-band in this experiment might have ensured that the coherence values were statistically significantly higher for a period of up to 36 days after an event.…”
Section: Groupsupporting
confidence: 90%
See 3 more Smart Citations
“…Increase of coherence after a mowing event is in line with a similar previous study that was based on X-band data and 1-day interferometric pairs [27]. In contrast to that study, the use of C-band in this experiment might have ensured that the coherence values were statistically significantly higher for a period of up to 36 days after an event.…”
Section: Groupsupporting
confidence: 90%
“…Precipitation up to 3-h before one or both of the image acquisitions changes the structure and dielectric constant of the vegetation on grassland, remarkably decreasing the coherence. Loss of coherence due to precipitation has also been reported by Zalite et al [27] and Ahmed et al [42]. At the same time, R58 and R80 geometries did not show any significant differences-the notches around the median that represent 95% confidence intervals are overlapping.…”
Section: Effect Of Precipitationsupporting
confidence: 78%
See 2 more Smart Citations
“…Studies have shown inverse relationships between vegetation height and coherence at various SAR frequencies, including at X-band and with COSMO SkyMed [60,61]. However, with X-band, complete temporal decorrelation is soon reached with vegetation growth and short temporal baselines are necessary to derive quantitative information on crop height [60,61].…”
Section: Coherencementioning
confidence: 99%